THE EDUCATIONAL MARKETING STRATEGY IS BASED ON THE COMPETITIVE ADVANTAGES OF PESANTREN - Hefniy, Hefniy; Arifin, Syamsul (Universitas Nurul Jadid, 2023)
This study describes the innovation of Islamic boarding school-based education marketing at MA Al Masduqiah. Marketing innovation is an important thing to do, considering the intense competition that is happening. This study used a qualitative approach to field research. Existing data obtained by means of observation, interviews and documentation. Informants in this study were obtained by purposive sampling technique, then get five informants. Among them are school principals, public relations department, teachers, guardians of new students, and guardians of old students. The analysis of the data uses Yin theory, that is, it does not require control over the events studied, it is enough just to observe and then explain. The research results obtained stated that Islamic boarding school-based education marketing innovation at MA Al Mashduqiah consisted of three things, namely analysis of market needs, school programs and the label of plus Islamic boarding school-based schools.